2015
DOI: 10.1083/jcb.2092oia68
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine signaling promotes hematopoietic stem and progenitor cell emergence

Abstract: Hematopoietic stem cells (HSCs) emerge from aortic endothelium via the endothelial-tohematopoietic transition (EHT). The molecular mechanisms that initiate and regulate EHT remain poorly understood. Here, we show that adenosine signaling regulates hematopoietic stem and progenitor cell (HSPC) development in zebrafish embryos. The adenosine receptor A 2b is expressed in the vascular endothelium before HSPC emergence. Elevated adenosine levels increased runx1 + /cmyb + HSPCs in the dorsal aorta, whereas blocking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 27 publications
0
23
0
Order By: Relevance
“…Besides its direct function as adhesion molecule, this membrane-bound enzyme catalyzes the extracellular conversion of adenosine monophosphate to adenosine. This pathway is particularly interesting in light of recent evidence for a functional role of adenosine signaling in HSC emergence in zebrafish (Jing et al, 2015). Moreover, adenosine receptor signaling was suggested to enhance cycling of hematopoietic progenitor cells (Pospísil et al, 2001), in line with the proposed impact of the sinusoids on HSC proliferation.…”
mentioning
confidence: 80%
“…Besides its direct function as adhesion molecule, this membrane-bound enzyme catalyzes the extracellular conversion of adenosine monophosphate to adenosine. This pathway is particularly interesting in light of recent evidence for a functional role of adenosine signaling in HSC emergence in zebrafish (Jing et al, 2015). Moreover, adenosine receptor signaling was suggested to enhance cycling of hematopoietic progenitor cells (Pospísil et al, 2001), in line with the proposed impact of the sinusoids on HSC proliferation.…”
mentioning
confidence: 80%
“…Moreover, since the Nlrp3 inflammasome is strongly activated by the extracellular purine nucleotide eATP, these effects on the HSPC response depend on purinergic signaling in which eATP is the principal stimulatory mediator [44,[55][56][57]. The role of purinergic signaling in hematopoietic development has been convincingly demonstrated by another group in a zebra fish model in the context of the prohematopoietic effects of the eATP metabolite extracellular adenosine (eAdo) [58].…”
Section: Does Nlrp3 Inflammasome Signaling Contribute To the Developmmentioning
confidence: 98%
“…Laboratory investigations have led to several important observations that helped clarify the molecular mechanisms underlying HSC development and activation. For example, adenosine signaling plays an evolutionary conserved role in HSC formation in vertebrates . Tzeng and colleagues demonstrated that the stroma‐secreted CXCL12 (stromal cell‐derived factor‐1) keeps the HSCs in a quiescent state and maintains them in the osteoblastic niche .…”
Section: Introductionmentioning
confidence: 99%